Manipulating the orientation of an organic adsorbate on silicon: a NEXAFS study of acetophenone on Si(0 0 1) - O'Donnell, Kane; Warschkow, O.; Suleman, A.; Fahy, A.; Thomsen, L.; Schofield, S. (Institute of Physics Publishing Ltd., 2015)
We investigate the chemical and structural configuration of acetophenone on Si(0 0 1) using synchrotron radiation core-level spectroscopy techniques and density functional theory calculations. Samples were prepared by vapour phase dosing of clean Si(0 0 1) surfaces with acetophenone in ultrahigh vacuum. Near edge x-ray absorption fine structure spectroscopy and photoelectron spectroscopy measurements were made at room temperature as a function of coverage density and post-deposition anneal temperature. We show that the dominant room temperature adsorption structure lies flat on the substrate, while moderate thermal annealing induces the breaking of Si-C bonds between the phenyl ring and the surface resulting in the reorientation of the adsorbate into an upright configuration.